2016
DOI: 10.1037/xhp0000213
|View full text |Cite
|
Sign up to set email alerts
|

The effects of alphabet and expertise on letter perception.

Abstract: Long-standing questions in human perception concern the nature of the visual features that underlie letter recognition and the extent to which the visual processing of letters is affected by differences in alphabets and levels of viewer expertise. We examined these issues in a novel approach using a same-different judgment task on pairs of letters from the Arabic alphabet with two participant groups—one with no prior exposure to Arabic and one with reading proficiency. Hierarchical clustering and linear mixed-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
60
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(74 citation statements)
references
References 70 publications
11
60
0
1
Order By: Relevance
“…Such confounds can in theory be controlled away, but this can be difficult with a small dataset (typically, the 26 or 52 letters of the Latin script). My re‐analysis of a classic study in letter perception (Podgorny & Garner, ) (see SM 2.10) detected a positive effect of letter cardinality on letter discrimination, in line with what previous studies have shown for the Latin and Arabic scripts (Fiset et al., ; Wiley et al., ). I also found a tendency for pure letters to be recognized faster than mixed ones (a feature that had not, to my knowledge, been investigated by previous studies).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Such confounds can in theory be controlled away, but this can be difficult with a small dataset (typically, the 26 or 52 letters of the Latin script). My re‐analysis of a classic study in letter perception (Podgorny & Garner, ) (see SM 2.10) detected a positive effect of letter cardinality on letter discrimination, in line with what previous studies have shown for the Latin and Arabic scripts (Fiset et al., ; Wiley et al., ). I also found a tendency for pure letters to be recognized faster than mixed ones (a feature that had not, to my knowledge, been investigated by previous studies).…”
Section: Discussionsupporting
confidence: 86%
“…Not necessarily. A letter's saliency inside a script depends crucially on non-visual factors, such as its frequency of use (New & Grainger, 2011) or the reader's expertise with the script (Wiley, Wilson, & Rapp, 2016). Also, appealing visual features may be present in many different letters of the same script (for instance, many Latin letters include a left-hand-side vertical bar, which makes them confusable).…”
Section: Discussionmentioning
confidence: 99%
“…By including visual (computed and stored), phonetic, and motoric similarity within the regression analyses, we were able to demonstrate—as would be predicted for purely symbolic representations—that this letter identity effect cannot be reduced to modality-specific visual, phonological or motor effects. This finding is also consistent with previous behavioral experimental evidence that cross-case letter forms share a common representation that is not modality-specific (e.g., Kinoshita & Kaplan, 2008; Wiley, Wilson, & Rapp, 2016). Consistent with the behavioral evidence of SLIs, Rothlein and Rapp (2014) provided neural data from an RSA analysis of fMRI data obtained from a letter decision task.…”
Section: Discussionsupporting
confidence: 92%
“…This finding reveals that diacritical marks are encoded very rapidly-note that most letters in Arabic differ only in the number/location of diacritical marks. As Wiley et al (2016) showed, diacritical marks are the most relevant element to discriminating letters in Arabic.…”
mentioning
confidence: 99%
“…As Davis (2010) indicated, future implementations of these models should incorporate a more sophisticated letter coding scheme to encode letter representations from their visual features. Three of the main challenges for modelers are how to specify (1) the most diagnostic visual elements of letters (e.g., lines, curves, intersections, terminations) in the initial phases of word processing (see Blais et al, 2009;Rosa, Perea, & Enneson, 2016, for discussion); (2) how these visual features are dynamically weighted (see Wiley, Wilson, & Rapp, 2016) 3 ; and (3) how visual information is mapped onto abstract representations (see Grainger et al, 2016). Although a thorough description of these questions would be beyond the scope of this study, it is clear that additional research is needed to help determine the time course of visual similarity effects across letters in during written-word recognition.…”
mentioning
confidence: 99%